REVEALING MDR RISK FACTORS AT THE JAYAPURA DISTRICT HEALTH OFFICE - Panggabean, Artha Beatrix; Hasmi, Hasmi; Makaba, Sarce; Irab, Semuel Piter; Boway, Dolfinus Y; Ruru, Yakob (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2024)
The proportion of MDR TB in Jayapura Regency in 2022 is 2.32% and the figure is higher than MDR TB in Papua Province, which is 151 cases. Treatment of MDR TB is more complex than drug-sensitive TB The purpose of this study was to determine the factors associated with the incidence of multidrug resistant tuberculosis (MDR TB) in patients with Pulmonary TB in the Health Office of Jayapura District, Papua Province. The type of case control study on the population of tuberculosis patients in the Jayapura Regency Health Office was 1,162 patients and samples were 27 cases and 54 controls. Data were obtained using medical record data and analyzed using chi square and logistic binary regression. The results showed that factors that were significantly associated with the incidence of MDR TB in patients with Pulmonary TB were side effects (p-value 0.000; OR = 9.1; CI95% (3.07 – 26.93), medication adherence (p-value 0.000; OR = 136; CI95% (25.45-724.06), duration of treatment (p-value 0.000; OR = 7.273; CI95% (2,546-20,773), treatment history in patients with Pulmonary TB in the Department (p-value 0.000; OR = 4.2; CI95% (8.801-21.991) and history of comorbidities (p-value 0.000; OR = 19.6; CI95% (5.79-66.34). Adherence to medication was the dominant factor in the incidence of MDR TB (p-value 0.000; OR = 36; CI95% (25,545 – 724,068). Conclusion: Adherence to taking medication is the dominant risk factor for MDR so it is recommended that in addition to PMO from Puskesmas need assistance from family. Studies have shown that TB patients who adhere to treatment are more likely to recover quickly and are no longer susceptible to other diseases than patients who do not adhere to treatment.